2006
DOI: 10.1021/jf052768e
|View full text |Cite
|
Sign up to set email alerts
|

Both Wheat (Triticum aestivum) Bran Arabinoxylans and Gut Flora-Mediated Fermentation Products Protect Human Colon Cells from Genotoxic Activities of 4-Hydroxynonenal and Hydrogen Peroxide

Abstract: Dietary fibers are fermented by the gut flora to yield short chain fatty acids (SCFAs), which inhibit the growth of tumor cells, induce glutathione S-transferases (GSTs), and protect cells from the genotoxic activity of 4-hydroxynonenal (HNE). Here, we investigated effects of wheat bran-derived arabinoxylans and fermentation products on these parameters of chemoprevention. Newly isolated water extractable (WeAx) and alkali extractable arabinoxylans (AeAx) were fermented under anaerobic conditions with human fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 50 publications
(74 reference statements)
7
64
0
2
Order By: Relevance
“…Type 2 diabetes risk (662) ; risk of weight and fat gains; large bowel cancer (66,75,106,266) ; satiating effect; cholesterol, bile acids, hormonal activity; immune system, toxicant transit; production of SCFA in the colon (663) ; SCFA, growth of tumour cells, glutathione-S-transferase and genotoxic activity of 4-hydroxynonenal (664) ; dilution of gut substances; energy content and glycaemic index of foods; insulin response; free radicals (93) Insoluble fibre (63) : antioxidant-bound phenolics and colon (150) ; faecal wet and dry weight and faecal bulking effect (660) ; intestinal transit (660) (107,108) ; fat absorption (665) ; bile salt pool size (666) ; cholesterol turnover (667) ; formation of carcinogenic metabolites from bile salts (269) ; precursor of lignans (221) ; anti-carcinogenic (265) Oligosaccharides (raffinose, stachyose and fructans) (295) :…”
Section: Appendixmentioning
confidence: 99%
“…Type 2 diabetes risk (662) ; risk of weight and fat gains; large bowel cancer (66,75,106,266) ; satiating effect; cholesterol, bile acids, hormonal activity; immune system, toxicant transit; production of SCFA in the colon (663) ; SCFA, growth of tumour cells, glutathione-S-transferase and genotoxic activity of 4-hydroxynonenal (664) ; dilution of gut substances; energy content and glycaemic index of foods; insulin response; free radicals (93) Insoluble fibre (63) : antioxidant-bound phenolics and colon (150) ; faecal wet and dry weight and faecal bulking effect (660) ; intestinal transit (660) (107,108) ; fat absorption (665) ; bile salt pool size (666) ; cholesterol turnover (667) ; formation of carcinogenic metabolites from bile salts (269) ; precursor of lignans (221) ; anti-carcinogenic (265) Oligosaccharides (raffinose, stachyose and fructans) (295) :…”
Section: Appendixmentioning
confidence: 99%
“…Nutritionally, they are classified under "unavailable carbohydrates" (dietary fiber) and are known to have beneficial effects in alleviating disease symptoms such as diabetes, atherosclerosis, and colon cancer [104]. Effects of wheat bran-derived arabinoxylans and fermentation products may act on chemoprevention [105].…”
Section: Arabinoxylanmentioning
confidence: 99%
“…Comet assay demonstrated that HNE, at concentration higher than 150 μM, displays a genotoxic effect in the colon carcinoma cell line HT-29 (Glei et al, 2006;Ebert et al, 2001;Knoll et al, 2005) and in HT29clone19A, a permanently differentiated sub-clone treated with sodium butyrate (Augeron & Laboisse, 1984). Moreover, such high doses of HNE were able to affect DNA integrity in primary human colon cells (Schaferhenrich et al, 2003;Glei et al, 2007) and in LT97, an established cell line derived from a differentiated microadenoma, representing a model of an early premalignant genotype, carrying adenomatous polyposis coli (APC) and Ki-ras mutated, but normal p53 (Richter et al, 2002), three well-characterized genes involved in coloncancer progression (Fearon et al, 1990).…”
Section: Genotoxicity and Mutagenicity Of Hne In Colon Cancermentioning
confidence: 99%
“…Similar results were obtained in HT-29 cells by using two wheat bran-derived arabinoxylans, fermented under anaerobic conditions in human feces. These two fermentation products inhibited growth and reduced the genotoxicity of HNE (100-200 μM) via up-regulation of the activity of GSTs, in absence of a GSTP1 or hGSTA4-4 increase (Glei et al, 2006). There is a growing interest in targeting aldose reductase (AR), as a novel therapeutic approach in preventing progression of colon cancer (Tammali et al, 2011).…”
Section: Hne Metabolism In Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation